A novel strategy to enhance the luminescence performance of NaGdF4:Ln3+ nanocrystals. Issue 23 (18th May 2016) - Song, Yan; Shao, Baiqi; Feng, Yang; Lü, Wei; Liu, Guixia; You, Hongpeng
Abstract : The emission intensity of the lanthanide doped ions in the NaGdF4 :Ln 3+ nanoparticles modified with BA and Phen ligands can be effective enhanced by the energy transfer from the Gd 3+ ions and surface modified ligands. Abstract : Promoting excitation efficiency is a direct route to enhance the luminescence properties of lanthanide doped materials. Here, we describe a novel strategy to enhance the luminescence performance of NaGdF4 :Ln 3+ (Ln = Tb, Eu, Dy) nanoparticles by surface modification with benzoate (BA) and 1, 10-phenanthroline (Phen) ligands via the sensitization of surface dopants. It was found that the surface ligands provide a new path for energy transfer to the activators due to the matching in energy levels between the two. Moreover, the overlap in excitation peaks for both Gd 3+ ions and ligands ensures the simultaneous energy transfer of Gd 3+ → Ln 3+ and ligands → Ln 3+ under a single wavelength excitation. The obtained NaGdF4 nanocomposite was characterized in detail using XRD, FT-IR, TGA, SEM, and EDS. The luminescence performance of the surface modified NaGdF4 :Ln 3+ nanoparticles was also optimized by tuning the loading amount of modified ligands. In addition, luminescence thermometry was realized by monitoring emission intensity at different temperatures.